On ℳ𝒜(i,j)-Continuous Functions in Biminimal Structure Spaces - Chawalit Boonpok; Chokchai Viriyapong; Montri Thongmoon; Nongluk Viriyapong (International Journal of Mathematics and Mathematical Sciences)
We introduce the notion of ℳ𝒜(i,j)-continuous functions and some other forms of continuity in biminimal structure spaces. Some new characterizations and several fundamental properties of ℳ𝒜(i,j)-continuous functions are obtained.